Les transformations de la vie sexuelle après cinquante ans : un vieillissement genré - Nathalie Bajos; Michel Bozon (Genre, Sexualité et Société)
In the past few decades, many changes have affected sexuality in the French society, notably among the elderly. Comparisons between surveys on sexual behavior carried out in 1970 and 2006 show that sexual activity after 50 has intensified and diversified over time and that differences in sexual attitudes and experiences of women and men have eroded. Yet a trend towards an earlier withdrawal of interest in sexuality is still experienced by women as soon as 50, when they leave the reproductive phase of their life, while men manifest a drop in interest for sex only ten years later, when they retire from work.